Daang pabalik - Santuico, Mariah Nicole Navaza 1995-; Santuico, Mariah Nicole Navaza; Lejano, Eduardo, Jr.; University of the Philippines Diliman. College of Mass Communication (2015)
"Daang Pabalik is a story about Maiya who has already experienced independence since she was young. She takes care of her grandmother who is getting older each day. Soon to be 21, Maiya undergoes fear of growing up and acieties of letting go of her childhood life. Due to this, Maiya continuously searches for the right mother figure that she could depend on. Receiving a letter from her mother, who abandoned her when she was ten, she decides to go on a journey to search for her. However, a little girl joins Maiya on her journey. Together, they hope to find acceptance for the past and courage for the future. The film focuses on a life situation which everyone has experienced or will eventually experience: transition to adulthood. It is a story of searching and finding the way back once we feel lost. Using the psychoanalytic framework, specifically the structural model of personality, the film discusses how the main character fears growing up through her own representations of id, ego, and superego. The film also follows the concept of 'social psychology of experience', focusing on the factors of how people remember and tend to forget."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Memory in motion pictures; Memory -- Social aspects; Psychoanalysis and motion pictures